Pengaruh electronic word ofmouth dan country of origin terhadap purchase decision produk skincare lokal serum wajah Somethinc - Anwar, Resa Nurlaela; Wardani, Widya Ayu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study was proposed to determine how much influence electronic word ofmouth and country oforigin have on the purchase decision oflocal skincare products Somethinc facial serum survey ofSomethinc consumers on twitter account followers @ohmybeautybank. The data collection method used was by giving questionnaires to 100 respondents of @ohmybeautybank twitter account followers who used Somethinc face serum at least 2 times in the last 2 months. The sample technique uses non-probability sampling and the analysis tool technique uses Simple Linear Regression and Multiple Linear. The results ofthis study indicate that electronic word ofmouth and country oforigin have an effect on purchase decisions. However, the effect is not significant. Partially electronic word ofmouth has an influence on purchase decision, and country oforigin has an influence on purchase decision.